Behaviour of a speargun with a novel muzzle - Comportamento di un fucile subacqueo con testata innovativa (Fracture and Structural Integrity, 2013)
The paper presents the results of a numerical and experimental investigation performed on a barrel of a speargun equipped with two kinds of muzzle. In particular, a standard muzzle for speargun (having an elastic propulsion) has been compared with an innovative one called ‘roller’. This new muzzle is equipped with two rollers and special bands. The rubber bands, fixed at the lower side of the barrel, run through the rollers and are engaged in suitable seats of the shaft. These bands are, therefore, longer than the traditional ones and,consequently, with equal force applied by the diver, the roller speargun has a longer range. Thanks to theparticular geometry of the new muzzle, one of the front constraints of the elastic bands is moved to the lowerpart of the barrel or the handle.As a consequence, the scheme of the loads applied on the speargun remarkably changes passing from a standard muzzle to a roller one. All that has a great influence on the level of deformation of the barrel and, consequently, on the accuracy of the shot. Because of the low velocity of the spear (if compared with the firearms), in fact, the accuracy of the shoot if strongly influenced by the barrel bending due to the forces applied by means of the elastic bands.
Keywords: Speargun